CoDesign for Public-Interest Services - Selloni, Daniela (Springer International Publishing : Imprint: Springer, 2017)
This books focuses on co-design, and more specifically, on the various forms co-design might take to tackle the most pressing societal challenges, introducing public-interest services as the main application field. To do so, it presents an extensive study conducted within a particular community of residents in Milan: this is a social innovation story integrated into the discipline of service design, which simultaneously deepens the related concepts of co-design, co-production and co-management of services. Drawing upon this experience and further studies, the book presents the idea of a collaborative infrastructure and its related infrastructuring process in ten steps, in order to explore the issues of incubation and replication of services and to extensively investigate the creation of those experimental spaces in which citizen participation is fostered and innovation in the public realm is pursued. Lastly, the book develops other lines of reflection on co-design seen, for example, as a form of cultural activism, as an instrument for building citizenship, and as a key competence for the public administration and thus as a public service itself. The idea of co-design as a way to regenerate the practices of democracy is a recurring theme throughout the book: co-design is a process that seeks to change the state of things and it is intentionally presented as a long and complex path in which the role of designer is not only that of a facilitator, but also that of a cultural operator who contributes with ideas and visions, hopefully fostering a real cultural change.
Keywords: Social sciences.; Service industries.; Assessment.; Sustainable development.; Welfare economics.; Social service.; elektronické knihy; electronic books